Graphene-infused terracotta acoustic sound amplifiers - T. R. Rajalekshmi; Shilpa Pavithran; Rinku Rani Das; Alex James (Scientific Reports)
Abstract This work introduces a novel approach for enhancing mobile audio performance by incorporating graphene-infused terracotta as an acoustic amplifier. Leveraging the high thermal conductivity and mechanical strength of graphene, this study demonstrates the design, fabrication, and acoustic characterization of terracotta amplifiers. We demonstrate the significant impact of graphene-infused terracotta amplifiers on improving sound amplification in addition to mechanical strength. A graphene-based dispersion is prepared for incorporation in clay to make the amplifier. Testing is carried out on normal and graphene-dispersion-incorporated terracotta amplifiers. The experimental results illustrate a substantial improvement in audio quality with increased volume compared to conventional terracotta-based mobile speakers. The frequency-dependent variation of the output signal, SNR, and the influence of submerging in water have also been studied. This work contributes to the field of acoustic materials and offers new possibilities for augmenting the auditory experience of mobile device users while also presenting sustainable and aesthetically appealing acoustic accessories.